Virtual reality for older people: effectiveness of a training program for accident prevention - Napetschnig, Alina; Deiters, Wolfgang; Brixius, Klara (Frontiers in Virtual Reality, 2025)
BackgroundAs people age, physical and cognitive limitations increasingly affect the daily mobility of older adults. Virtual reality (VR) applications offer novel opportunities for senior citizens to enhance their functional abilities. Routine activities, like crossing a street, can be simulated and practiced within a virtual environment.ObjectiveThis intervention study investigated the impact of a VR training application (‘Wegfest’) on physical function, fall-related confidence, and cognitive status in senior citizens. It was hypothesized that participation in the VR-based training program would lead to improvements in functional mobility, fall-related self-confidence, and cognitive performance.MethodFor this study, the VR application ‘Wegfest’ was developed to simulate various road scenarios. Over a 4-week training period, senior citizens practiced navigating diverse road-crossing situations. The effectiveness of the application was evaluated through measures of physical and cognitive performance, including the Timed Up and Go (TUG) Test, the Falls Efficacy Scale-International (FES-I), and the Montreal Cognitive Assessment (MoCA). In total, 29 senior citizens (M = 74.95 years) were recruited, with 20 participants included in the final analysis. Data collection and statistical analyses were performed using a database specifically created for Wegfest.ResultsThe VR application “Wegfest” received positive feedback from participants. Significant improvements were found between pre- and post-intervention measurements for TUG, t (19) = 3.50, p = 0.002, and for FES-I, z = −2.82, p = 0.005. No significant differences were observed in MoCA scores, z = 0.58, p = 0.564.ConclusionVirtual reality (VR) shows promise as an effective tool for supporting older adults in their daily activities. As a pilot (exploratory) study with a small sample size and a relatively high dropout rate, the results should be interpreted as preliminary and indicative rather than conclusive. The lack of behavioral outcome measures further underscores the exploratory nature of this investigation. Further research with larger samples and more comprehensive outcome measures is needed to evaluate the effectiveness and generalizability of ‘Wegfest’ and similar VR applications for enhancing everyday mobility.